THE FACTORS AFFECTING OF STUNTING IN AGE 6-24 MONTHS - Fitri Wahyuni; Fauzi Arasj; Fanny Fitrahmisasty; Singgih Elva Putra (JURNAL KESEHATAN MERCUSUAR, 2019)
The prevalence of stunting in Indonesia in 2018 reaches 30.8%. According to data from the Padang City Health Office in 2017, toddlers with the most stunting conditions in Padang City were in Pauh District as many as 96 toddlers. This is influenced by many factors that can have a bad impact on the child's future. This study aims to determine the factors that influence the incidence of stunting in infants aged 6-24 months. This research is a quantitative study using a cross sectional design with 66 respondents aged 6 - 24 months in Limau Manis Selatan Village, Pauh District. The research will be conducted from May to July 2019. Sampling with purposive sampling technique. The results showed that the factor most related to the incidence of stunting was poor hygiene with a percentage of 48.5% (p value = 0.037). The conclusion of this study all factors have a relationship with the incidence of stunting in infants. Suggestions for health services are expected to be able to provide counseling to mothers and bring toddlers to health services when toddlers are sick so that they can be addressed appropriately.